Frozen : the junior novelization - Nathan, Sarah; Roman, Sela (New York : Random House, 2013)
When a prophecy traps a kingdom in eternal winter, Anna team up with Kristoff to find Anna's sister, the Snow Queen Elsa, and put an end to her icy spell.
RL: 4.0.
Keywords: Princesses -- Juvenile fiction; Sisters -- Juvenile fiction; Ice -- Juvenile fiction; Snow -- Juvenile fiction; Quests (Expeditions) -- Juvenile fiction; Fantasy fiction